The effects of a nonlinear pedagogy training program in the technical-tactical behaviour of youth futsal players - Pizarro, D.; Praxedes, A.; Travassos, B.; del Villar, F.; Moreno, A. (International Journal of Sports Science & Coaching, 2019)
The aim of this study was to analyse the effect of an intervention program, based on nonlinear pedagogy, on the decisionmaking and execution of different actions in futsal. The intervention program consisted of 12 training sessions. A quasiexperimental study was developed with eight male futsal players (M=15.375, SD=0.517). The GPET instrument was used to analyse the decision-making and execution of 3442 actions measured during competitive matches (pass, dribbling and shooting). Both variables were analysed with regard to the three tactical principles of attack: keep the ball possession, progression towards the goal and shooting at goal with the lowest level of opposition. With respect to the pass, results showed significantly higher values in decision-making and execution in the first and second principles, but not in the third one. In the dribbling action, results showed significantly higher values in decision-making in the second and third principle, but not in the first one. However, no significant differences were found in the shooting actions. These findings suggest that coaches should take into account in the task design, the tactical principles of play to develop tactical behaviour of youth futsal players.